THE GEOCHEMICAL CHARACTERISTIC OF MAJOR ELEMENT OF GRANITOID OF NATUNA, SINGKEP, BANGKA AND SIBOLGA - Ediar Usman (BULLETIN OF THE MARINE GEOLOGY, 2015)
A study of geochemical characteristic of major elelemnt of granitoid in Western Indonesia Region was carried out at Natuna, Bangka, Singkep and Sibolga. The SiO2 contents of the granites are 71.16 to 73.02 wt%, 71.77 to 75.56wt% and 71.16 to 73.02wt% at Natuna, Bangka, and Singkep respectively, which are classified as acid magma. While in Sibolga the SiO2 content from 60.27 to 71.44wt%, which is classified as intermediate to acid magma. Based on Harker Diagram, the granites from Natuna, Bangka and Singkep as a co-genetic. In other hand the Sibolga Granite show as a scatter pattern. Granites of Natuna, Bangka and Singkep have the alkaline-total (Na2O + K2O) between 6.03 to 8.51 wt% which are classified as granite and alkali granite regime. K2O content ranges from 3.49 to 5.34 wt% and can be classified as calc-alkaline type. The content of alkaline-total of Sibolga granite between 8.12 to 11.81 wt% and classified as a regime of syenite and granite. The range of K2O is about 5.36 to 6.94wt%, and assumed derived from high-K magma to ultra-potassic types. Granites of Natuna, Bangka and Singkep derived from the plutonic rock types and calc-alkaline magma, while Sibolga granite magma derived from K-high to ultra-potassic as a granite of islands arc. Based on the chemical composition of granite in Western Indonesian Region can be divided into two groups, namely Sibolga granite group is representing the Sumatera Island influenced by tectonic arc system of Sumatera Island. Granites of Bangka and Singkep are representing a granite belt in Western Indonesian Region waters which is influenced by tectonic of back arc.Keywords: magma, geochemical characteristic, major element and Western Indonesian Region Kajian karakteristik geokimia dari unsur utama granitoid di Kawasan Barat Indonesia telah dilakukan di daerah Natuna, Bangka, Singkep dan Sibolga. Kandungan SiO2 granit Natuna antara 71,16 - 73,02%, Bangka antara 71,77 - 75,56%, Singkep antara 72,68 - 76,81% termasuk dalam magma asam. Granit Sibolga memiliki kandungan SiO2 antara 60,27 - 71,44% termasuk dalam magma menengah - asam. Berdasarkan Diagram Harker, granit Natuna, Bangka dan Singkep mempunyai asal kejadian yang sama (ko-genetik), sedangkan granit Sibolga membentuk pola pencar. Granit Natuna, Bangka dan Singkep mengandung total alkalin (K2O+Na2O) antara 6,03 - 8,51% termasuk dalam jenis rejim granit dan alkali granit. Berdasarkan kandungan K2O antara 3,49 - 5,34 %berat, bersifat kalk-alkali. Granit Sibolga mengandung total alkali antara 8,12 - 11,81% termasuk dalam rejim syenit dan granit, dan berdasarkan kandungan K2O antara 5,36 - 6,94% berasal dari jenis magma K-tinggi sampai ultra-potassik. Granit Natuna, Bangka dan Singkep berasal dari jenis batuan beku dalam dan magma kalk-alkalin yang berhubungan dengan penunjaman, sedangkan granit Sibolga berasal dari jenis magma K-tinggi - ultra-potassik sebagai granit busur kepulauan. Berdasarkan komposisi unsur kimia utama, granit di Kawasan Barat Indonesia dapat dibagi dalam dua, yaitu granit Sibolga yang mewakili P. Sumatera, dipengaruhi oleh sistem tektonik busur P. Sumatera. Granit Bangka dan Singkep dapat mewakili suatu jalur granit di perairan Kawasan Barat Indonesia yang dipengaruhi oleh tektonik busur belakang. Kata kunci: jenis magma, karakteristik geokimia, unsur utama, dan Kawasan Barat Indonesia